Strategi Pemelajaran N3: Pemanfaatan Modul JLPT N3 untuk Meningkatkan Kompetensi Guru Bahasa Jepang Tingkat SMA/Sederajat Se-Jabodetabek - Indun Roosiani; Hargo Saptaji; Alifia Masitha Dewi; Yosefa Putri Tanjungsari; Rahma Fitri Alifah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Japanese language teachers play an important role in improving the quality of learning at senior high schools or equivalent institutions. However, many teachers in the Greater Jakarta area still have not mastered Japanese at the JLPT N3 level, particularly in the aspects of moji (kanji) and goi (vocabulary). This condition affects the quality of learning, including students’ limited exposure to proper Japanese and their low confidence in communication. Based on discussions with partner teachers, the main challenge lies in mastering moji and goi as the foundation for understanding bunpō (grammar) and dokkai (reading comprehension). Therefore, this community service program aims to improve teachers’ competence through the development of a JLPT N3 learning module based on moji-goi. The module is equipped with brief explanations, learning strategies, and a digital question bank to support independent learning. The implementation methods include needs assessment, module development and trial, finalization, mentoring, and evaluation. The expected outputs are an ISBN-registered module, intellectual property rights (IPR), and a scientific publication that are expected to improve the quality of Japanese language learning in secondary schools.